Arctic shipping - a study on feasibility and future impact on warehousing/shipping routes/shipbuilding - Wong, Suet Peng. (2011)
Sailing through the Arctic Ocean via the Northern Sea Route (NSR) gives a saving of around 40% on the sailing distance from East Asia (Yokohama) to Northern Europe (Hamburg) as compared to the current Suez Canal route. However, this 40% reduction in distance does not correspond to a 40% of cost saving due to many factors, such as higher construction cost for ice-classed vessels, non-regularity of schedule due to the ever-changing ice conditions, slower sailing speed, navigation difficulties, higher risk, hefty icebreaking service fees and etc.In this research study, NSR’s economic feasibility is examined using voyage simulation where 4,300 TEU container ships (normal open water, normal ice-classed and Aker Arctic double-acting ship) are employed, each make year round service between Yokohama and Hamburg. The annual total cost per TEU shipped by normal open water ship via Suez Canal is compared to the annual total cost per TEU shipped incurred from the ice-classed ships (normal ice-classed and Aker Arctic double-acting ship), taking NSR during the navigable months and Suez Canal for the rest of the year. To make this study flexible, length of NSR navigation season has been divided into three options (3/6/9 months per year).